2003
DOI: 10.1046/j.1440-1819.2003.01141.x
|View full text |Cite
|
Sign up to set email alerts
|

Classification of frequency distributions of diagnostic criteria scores in twelve personality disorders by the curve fitting method

Abstract: The purpose of the present study was to investigate whether each personality disorder (PD) has a different frequency distribution of diagnostic criteria, and to classify the distribution of each PD on the basis of shape by the curve fitting method. A total of 4740 male subjects in early adulthood completed the Korean version of the Personality Diagnostic Questionnaire (4th revision; PDQ-4 + ). The frequency distribution of scores in each PD was specified to the best fitted model by the curve estimation procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…16 Only one other group seems to have approached attributes relating to paranoia in this way, albeit by using conventional categories of personality disorder. 31 They found a slightly different (cubic) curve of distribution for items forming the diagnostic criteria for paranoid personality disorder (the item count with the highest frequency was 2 rather than 0).…”
Section: Discussionmentioning
confidence: 97%
“…16 Only one other group seems to have approached attributes relating to paranoia in this way, albeit by using conventional categories of personality disorder. 31 They found a slightly different (cubic) curve of distribution for items forming the diagnostic criteria for paranoid personality disorder (the item count with the highest frequency was 2 rather than 0).…”
Section: Discussionmentioning
confidence: 97%
“…The lack of clear demarcation between cases and non-cases detected in taxonometric analysis could help explain the low inter-rater reliability found using clinical diagnostic criteria. On the other hand, a Korean study examining the frequency distribution of personality disorder criteria found that PPD exhibits a cubic distribution [42]. These results suggest that PPD is intermediate between disorders that are categorical, such as Antisocial and Schizoid, and those that are more clearly dimensional, such as Obsessive-Compulsive.…”
Section: Dimensionsmentioning
confidence: 99%
“…Therefore it cannot represent the general population, but it can avoid the gender bias in assessment of personality disorder and effect of gender and age in temperament and character development. But by the same reason, our findings have some limitations when generalizing to female subjects, other age groups and other ethnic groups 12 . Interpretation must be done with caution regarding this result.…”
Section: Discussionmentioning
confidence: 61%
“…There have been several trials to develop personality systems to solve these problems, 10–12 and the Cloninger et al. concept of temperaments and characters is one of them 13 .…”
Section: Introductionmentioning
confidence: 99%